2000
DOI: 10.1038/sj.mp.4000819
|View full text |Cite
|
Sign up to set email alerts
|

DRD4 and DAT1 as modifying genes in alcoholism: interaction with novelty seeking on level of alcohol consumption

Abstract: in genotype distribution. The 2-2 genotype was present in three out of 26 patients with dyskinesia (11.5%) vs eight out of 30 patients without dyskinesia (26.7%; P = 0.19). Due to the lower frequency of the 2.2 genotype, together with an over-representation of the 1-2 genotype among the dyskinesia-positive subjects (see above), the overall distribution (2 × 3 table) of the 1-1, 1-2 and 2-2 genotypes was almost significantly different in the dyskinesia-positive vs dyskinesia-negative schizophrenic patients (P =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 14 publications
1
43
0
2
Order By: Relevance
“…This was between avoidance traits and the 5HTT LPR polymorphism (P ¼ 0.038). A crude estimate of the effect size of 26 Control participants not scored for personality Benjamin et al 34 Data reported elsewhere Benjamin et al 43 Subscale data reported only Blairy et al 45 Too few papers reporting data on this gene to analyse Comings et al 36 Data reported elsewhere Comings et al 19 Subscale data reported only Comings et al 47 Too few papers reporting data on this gene to analyse Damberg et al 48 Subscale data reported only Deary et al 27 Extreme scores design Duaux et al 32 Data not released Ekelund et al 28 Extreme scores design Gustavsson et al 57 Subscale data reported only Jang et al 40 Data reported elsewhere Jonsson et al 63 Subscale data reported only Jonsson et al 62 Subscale data reported only Jonsson et al 61 Subscale data reported only Jonsson et al 29 Subscale data reported only Jorm et al 65 Too few papers reporting data on this gene to analyse Lerman et al 31 Data not released Manuck et al 73 Too few papers reporting data on this gene to analyse Manuck et al 72 Too few papers reporting data on this gene to analyse Mel et al 35 Data reported elsewhere Melke et al 74 Subscale data reported only Nielsen et al 77 Subscale data reported only Persson et al 30 Subscale data reported only Persson et al 81 Too few papers reporting data on this gene to analyse Ricketts et al 83 Data reported elsewhere Sher et al 38 Data reported elsewhere Sirota et al 37 Data reported elsewhere Strobel et al 24 Data reported elsewhere Tsai et al 89 Too few papers reporting data on this gene to analyse Vandenbergh et al 90 Extreme scores design the 5HTT LPR polymorphism on avoidance traits suggested that the genotypic effect accounted for less than 10% of the phenotypic variance, but this figure should ...…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was between avoidance traits and the 5HTT LPR polymorphism (P ¼ 0.038). A crude estimate of the effect size of 26 Control participants not scored for personality Benjamin et al 34 Data reported elsewhere Benjamin et al 43 Subscale data reported only Blairy et al 45 Too few papers reporting data on this gene to analyse Comings et al 36 Data reported elsewhere Comings et al 19 Subscale data reported only Comings et al 47 Too few papers reporting data on this gene to analyse Damberg et al 48 Subscale data reported only Deary et al 27 Extreme scores design Duaux et al 32 Data not released Ekelund et al 28 Extreme scores design Gustavsson et al 57 Subscale data reported only Jang et al 40 Data reported elsewhere Jonsson et al 63 Subscale data reported only Jonsson et al 62 Subscale data reported only Jonsson et al 61 Subscale data reported only Jonsson et al 29 Subscale data reported only Jorm et al 65 Too few papers reporting data on this gene to analyse Lerman et al 31 Data not released Manuck et al 73 Too few papers reporting data on this gene to analyse Manuck et al 72 Too few papers reporting data on this gene to analyse Mel et al 35 Data reported elsewhere Melke et al 74 Subscale data reported only Nielsen et al 77 Subscale data reported only Persson et al 30 Subscale data reported only Persson et al 81 Too few papers reporting data on this gene to analyse Ricketts et al 83 Data reported elsewhere Sher et al 38 Data reported elsewhere Sirota et al 37 Data reported elsewhere Strobel et al 24 Data reported elsewhere Tsai et al 89 Too few papers reporting data on this gene to analyse Vandenbergh et al 90 Extreme scores design the 5HTT LPR polymorphism on avoidance traits suggested that the genotypic effect accounted for less than 10% of the phenotypic variance, but this figure should ...…”
Section: Discussionmentioning
confidence: 99%
“…25 In the case of five studies, correspondence with the authors indicated that it would not be possible to include their data in the metaanalysis. [26][27][28][29][30] In one case, the ethical approval granted to the study did not allow the data to be released 31 and in one case there was no response from the authors. 32 For each study, the following data were extracted: Data were extracted separately for papers where data on more than one gene, or more than one personality scale, were reported.…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Bau et al described an interaction effect between DRD4 and DAT1 genotypes with novelty seeking on the level of alcohol consumption. 18 In case of Marques et al, an association between comorbid major depressive disorder, drug abuse and nicotine dependence with the short allele of the promoter region of the serotonin transporter gene (SLC6A4) was suggested in a sample of 114 patients with alcohol dependence and 218 controls. 19 Freire et al studied a group of 100 smoking alcoholics, 120 non-alcoholic smokers and 112 non-smoking controls, and demonstrated that alcoholic and non-alcoholic smokers have higher frequency of the DRD2 gene TaqI A1 allele than non-smoking controls. 20 Also, they demonstrated that individuals who had at least one dopamine beta-hydroxylase (DBH) 1021T allele smoked fewer cigarettes per day than those individuals with CC homozygote.…”
Section: Research Groups and Their Main Findings In The Brazilian Popmentioning
confidence: 99%
“…The final response rate adjusted for ineligible cases was 62.3% (n ϭ 1120). Members of the sample of 1120 were somewhat less likely to be younger physicians (age [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] and women compared with national estimates. Respondents were randomized to one of two survey instruments, which presented a new test to tailor smoking cessation treatment as a genetic or a nongenetic test.…”
Section: Survey Overviewmentioning
confidence: 99%